The things we leave unfinished / Rebecca Yarros. - Yarros, Rebecca (Penguin Books, 2022)
Twenty-eight-year-old Georgia Stanton has to start over. Having survived a brutal marriage, she gave almost everything - the New York house, the friends, and her pride - to her ex, simply to speed along the brutal and public divorce. She may have been raised by arguably one of the greatest writers of the twentieth century, Scarlett Stanton, but it turns out that love in the real world is nothing like her grandmother's novels. After moving home to her tiny Colorado town in search of peace and quiet, she discovers her mother had found Scarlett's final, unpublished manuscript amid a box of old letters, and sent it to her eager publisher. Her very unfinished manuscript. The catch? The publisher can only finish and publish the manuscript if Georgia agrees.